2019
DOI: 10.1152/ajpendo.00277.2018
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic endotoxemia promotes adipose dysfunction and inflammation in human obesity

Abstract: Impaired adipose tissue (AT) lipid handling and inflammation is associated with obesity-related metabolic diseases. Circulating lipopolysaccharides (LPSs) from gut microbiota (metabolic endotoxemia), proposed as a triggering factor for the low-grade inflammation in obesity, might also be responsible for AT dysfunction. Nevertheless, this hypothesis has not been explored in human obesity. To analyze the relationship between metabolic endotoxemia and AT markers for lipogenesis, lipid handling, and inflammation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 50 publications
1
40
0
Order By: Relevance
“…In fact, excessive calorie intake increases fat accumulation and the lipotoxicity activates the production of cytokines and the cells involved in innate immunity. This production promotes a chronic, low-grade inflammatory status, induces recruitment, and activation of mature immune cells and other cells, such as macrophages and adipocytes, respectively, which modify the tissue and reinforce the inflammatory response [12,48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, excessive calorie intake increases fat accumulation and the lipotoxicity activates the production of cytokines and the cells involved in innate immunity. This production promotes a chronic, low-grade inflammatory status, induces recruitment, and activation of mature immune cells and other cells, such as macrophages and adipocytes, respectively, which modify the tissue and reinforce the inflammatory response [12,48].…”
Section: Discussionmentioning
confidence: 99%
“…The intestinal barrier dysfunction causes an increased circulation of lipopolysaccharides (LPS) derived from gram-negative bacteria [10,11]. In turns, LPS spread participates in metabolic endotoxemia development, adipose tissue dysfunction, and systemic inflammation, triggering obesity-related complications [12].…”
Section: Introductionmentioning
confidence: 99%
“…For one, lipopolysaccharide (LPS) derived from the cell wall of pathogenic Gram-negative microbes can bind toll-like receptors (TLRs) in mucosal and peripheral tissues, initiating pro-inflammatory signaling cascades [56,57]. Data from both human and rodent studies has linked an obese phenotype to elevated circulating levels of plasma LPS, a condition known as metabolic endotoxemia [58][59][60]. For example, in a comparative study of human subjects, baseline circulating endotoxin levels were found to be 20% higher in obesity or glucose intolerant individuals and 125% higher in type 2 diabetics compared to lean subjects [61].…”
Section: Regulation Of Immune Functionmentioning
confidence: 99%
“…When there are disturbances in the barrier function and mucosal immune homeostasis, the influx of intestine luminal content triggers an exaggerated mucosal immune response [1]. Ultimately, chronic exposition to these detrimental environmental stimuli may lead to the development of local and systemic inflammatory conditions [2,3].…”
Section: Introductionmentioning
confidence: 99%